Liability, Market Cap Terhadap WACC - Hurian Kamela (Pusat P2M Politeknik Negeri Batam, 2021)
WACC is a measurement indicator that describes capital financing in a company. If the movement of shares is higher, the WACC value is not good in the company because the burden increases, the WACC value that the company has must be smaller so that the company can carry out its obligations, especially regarding share payments. The purpose of this study is to analyze the factors that affect the WACC in the company, namely liabilities (company debt), market capitalization (market capitalization). The research method used is multiple linear regression. Secondary data, namely financial reports and data streams (Thomson Reuters) were analyzed and calculated using stata. The number of samples taken was 17 banking companies during the 5 year period (2015-2019). The results of this study explain that liabilities, market cap have no effect on WACC, this can be because market conditions do not depend on the amount of company debt, market capitalization, because other external factors such as trust in companies and investors' confidence in the banking sector are increasing and developing.